2012
DOI: 10.1093/icvts/ivr106
|View full text |Cite
|
Sign up to set email alerts
|

What is the role of screening in the management of abdominal aortic aneurysms?

Abstract: A best-evidence topic in vascular surgery was written according to a structured protocol. The question addressed was whether screening asymptomatic individuals for an abdominal aortic aneurysm (AAA) is feasible and improves disease-free survival. Seven studies presented the best evidence to answer the clinical question. The author, journal, date and country of publication, patient group studied, study type, relevant outcomes, results and limitations of the studies are tabulated. In total, four randomized popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 20 publications
0
7
0
1
Order By: Relevance
“…19 Esta conclusão já tinha sido obtida numa MA anterior (Lindholt et al); 10 como também a alguns aspetos da RS da Cochrane, uma vez que nestas revisões foram incluídos dados relativos às mortes de um ECAC (Western Australia) não ajustados para a idade. 18,20 Foram ainda incluídas 7 NOC, a maioria realizadas no norte da América (quadro III). Ferket et al realizaram uma análise qualitativa de muitas das NOC incluídas nesta revisão, tendo sido aquelas com pontuações de rigor mais elevadas a da USPSTF (79%), da American College of Cardiology/American Heart Association (ACC/AHA) (63%) e a do National Screening Committee (NSC) (41%).…”
Section: Resultsunclassified
“…19 Esta conclusão já tinha sido obtida numa MA anterior (Lindholt et al); 10 como também a alguns aspetos da RS da Cochrane, uma vez que nestas revisões foram incluídos dados relativos às mortes de um ECAC (Western Australia) não ajustados para a idade. 18,20 Foram ainda incluídas 7 NOC, a maioria realizadas no norte da América (quadro III). Ferket et al realizaram uma análise qualitativa de muitas das NOC incluídas nesta revisão, tendo sido aquelas com pontuações de rigor mais elevadas a da USPSTF (79%), da American College of Cardiology/American Heart Association (ACC/AHA) (63%) e a do National Screening Committee (NSC) (41%).…”
Section: Resultsunclassified
“…Regarding mortality from rAAA, the number needed to screen (NNS) for AAA to avoid one death in rAAA is 238, with corresponding figures for colorectal---and breast---cancer being 671 and 1339 respectively (Dabare et al 2012). …”
Section: The Systematic Reviews and Meta-analysesmentioning
confidence: 99%
“…Screening for abdominal aortic aneurysm (AAA) in men aged 65 years using portable ultrasonography has been launched recently in Scotland and elsewhere in the UK. The effectiveness of AAA screening in men is supported by evidence from four randomized clinical trials, which have demonstrated that screening reduces AAA‐related deaths, but without any impact on overall mortality. Uptake among invited men in these four clinical trials ranged from 70 to 80 per cent.…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of AAA screening in men is supported by evidence from four randomized clinical trials, which have demonstrated that screening reduces AAA‐related deaths, but without any impact on overall mortality. Uptake among invited men in these four clinical trials ranged from 70 to 80 per cent. AAA screening in the Grampian region of north‐east Scotland was launched in October 2012 as part of a national population‐based screening programme.…”
Section: Introductionmentioning
confidence: 99%